TEDI’S BEHAVIOR CHANGE MODEL TO IMPROVING BRUSHING TEETH BEHAVIOR PARENTS - Purnama, Tedi; Rasipin, Rasipin; Ngatemi, Ngatemi (Postgraduate Program , Poltekkes Kemenkes Semarang, 2020)
The dental health problems of preschool children are higher compared to primary schools, this is due to children not being able to do independent activities in brushing their teeth. The right behavior change strategy can be carried out by providing dental health education by parents and teachers using learning methods and media tailored to the child's development. Tedi's behavior change is a model of learning to brush teeth in an effort to establish preschooler brushing behavior with 10 days. This study aims to produce a model of tedi's behavior change as an effort to form the teeth brushing behavior of preschool children. Method: this research uses Research and Development (R&D) and the test model uses quasy experiment pretest and posttest with control group design. The subjects of preschool children were divided into 3 groups: 1. Intervention of behavior change model 2. Model of tooth brushing 21 days as a control 3. Model of brushing teeth 1 day. Independent variables: tedi's behavior change model and the dependent variable: knowledge, attitudes and actions to brush parents' teeth. Data were tested using the intraclass correlation coefficient, repeated measure anova, friedman, one way anova and Kruskal wallis. Results: The implementation of Tedi's behavior change model training was equally effective with a 21-day brushing model (p> 0.05) compared to a 1-day brushing model (p <0.005). Conclusion: The implementation of Tedi's behavior change model training is effective in improving parents' brushing behavior.